2018
DOI: 10.1016/j.tourman.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Power and empowerment: How Asian solo female travellers perceive and negotiate risks

Abstract: In response to the emergence of the solo female travel market in Asia, this study explores how Asian women perceive and negotiate the risks of travelling alone and the meanings of these processes. The lived experiences of 35 solo female travellers from 10 East and Southeast Asian countries were analysed using constructivist grounded theory.The findings reveal that Asian solo female travellers were concerned about gendered (e.g. sexual assault and street harassment) and racialised (e.g. discrimination and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 67 publications
(92 reference statements)
2
56
0
Order By: Relevance
“…While Wilson and Little's (2013) argument is mainly based on attributing women's fear of violence and sexual attack to perception, this is justified as women continue to be the primary victims of rape and sexual attack around the world (World Health Organization, 2014). The perception of fear still prevails among women travellers as their use of public space continues to remain regulated by a patriarchal system dictating what is 'appropriate' female travel behaviour (Brown and Osman, 2017;Jordan and Gibson, 2005;Wilson and Little, 2005;Yang et al, 2018b).…”
Section: Solo Travellers: Motivations and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…While Wilson and Little's (2013) argument is mainly based on attributing women's fear of violence and sexual attack to perception, this is justified as women continue to be the primary victims of rape and sexual attack around the world (World Health Organization, 2014). The perception of fear still prevails among women travellers as their use of public space continues to remain regulated by a patriarchal system dictating what is 'appropriate' female travel behaviour (Brown and Osman, 2017;Jordan and Gibson, 2005;Wilson and Little, 2005;Yang et al, 2018b).…”
Section: Solo Travellers: Motivations and Challengesmentioning
confidence: 99%
“…Research has paid more attention to the constraints faced by western women than Asian female solo travellers. Exceptions include research conducted in recent years by scholars, who studied the influence of Asian cultural norms on female travel behaviour (Seow and Brown, 2018;Teo and Leong, 2006;Yang, 2016;Yang et al, 2018aYang et al, , 2018bZhang and Hitchcock, 2017). Asian women have been cast as vulnerable and dependent in comparison with western women; thus, they seem to participate less in independent travel (Yang, 2016).…”
Section: Solo Travellers: Motivations and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of resistance is found in other studies of female travel. For example, Seow and Brown (2018) and Yang et al (2016) observed that for female Asian tourists, the very act of travelling solo was an expression of their resistance to cultural expectations of women.…”
Section: The Benefits Of Travel For Womenmentioning
confidence: 99%
“…Vaidyanathan et al (2018) also suggest that women may engage in superstitious behavior for "protective" reasons, with little actual belief in the effectiveness of superstitions. Women and especially solo traveling women generally feel more vulnerable and at risk when in unfamiliar locations (Yang et al, 2018). Even they may not openly endorse the superstitious beliefs, women may choose to act superstitiously to maintain their peace of mind.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%